Efektivitas Multimedia Interaktif Berbasis Microsoft Power Point Untuk Meningkatkan Kecerdasan Logika Matematika Anak Usia Dini - Tami Aspi Zahda Hidayah; Nandhini Hudha Anggarasari; Fajar Nugraha (JURNAL PAUD AGAPEDIA, 2023)
Mathematical logic intelligence certainly means a child's life. This mathematical logic intelligence is certainly expected to be well stimulated. Packaging of educational activities that are fun and unique and suitable for children's growth must be observed so that education is more meaningful and can achieve educational goals that have been planned optimally. Success in stimulating mathematical logic intelligence certainly depends on the teaching materials used. The purpose of this research is to determine the effectiveness of using interactive multimedia based on Microsoft power point to improve the mathematical logic intelligence of children aged 5-6 years. The research procedure used is a quasi-experimental design with a Noneequivalent control group design. There is also a research position in Setiamulya Village, Tamansari District, Tasikmalaya City by using the Purposive Sampling procedure. The final result of the research obtained a significance of 0,000 0, 05 which proves that there is a significant difference in children's mathematical logic intelligence after the use of interactive multimedia based on Microsoft power point in the experimental group and the control group who were treated using conventional media. Until then there is the effectiveness of using interactive multimedia based on Microsoft power point to improve the mathematical logic intelligence of children aged 5-6 years in Kindergarten located in Setiamulya Village, Tamansari District, Tasikmalaya City. Kecerdasan logika matematika pastinya berarti untuk kehidupan seseorang anak. Kecerdasan logika matematika ini pastinya diharapkan terstimulasi dengan baik. Pengemasan aktivitas pendidikan yang mengasyikkan serta unik dan cocok dengan pertumbuhan anak wajib dicermati supaya pendidikan lebih bermakna serta dapat menggapai tujuan pendidikan yang telah direncakan dengan optimal. Keberhasilan dalam menstimulasi kecerdasan logika matematika pastinya bergantung pada bahan ajar yang digunakan. Tujuan riset ini ialah guna mengetahui efektivitas pemakaian multimedia interaktif berbasis Microsoft power point buat meningkatkan kecerdasan logika matematika anak umur 5- 6 Tahun. Tata cara riset yang digunakan ialah quasi eksperimental design dengan desain Nonequivalent control group design. Ada pula posisi penelitiannya ialah di Kelurahan Setiamulya Kecamatan Tamansari Kota Tasikmalaya dengan memakai tata cara Sampling Purposive. Hasil akhir riset diperoleh signifikansi 0, 000 0, 05 yang membuktikan kalau ada perbedaan kecerdasan logika matematika anak yang signifikan sehabis pemakaian multimedia interaktif berbasis Microsoft power point pada kelompok eksperimen serta kelompok kontrol yang diberi perlakuan memakai media konvensional. Hingga dari itu ada efektivitas dari pemakaian multimedia interaktif berbasis Microsoft power point guna meningkatkan kecerdasan logika matematika anak umur 5- 6 tahun di Taman Kanak- kanak yang terdapat di Kelurahan Setiamulya Kecamatan Tamansari Kota Tasikmalaya.